2012
DOI: 10.9735/0976-5530.3.4.154-160
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENCE OF Enterococcus SPECIES FROM VARIOUS CLINICAL SPECIMENS IN SHRI SATHYA SAI MEDICAL COLLEGE AND RESEARCH INSTITUTE WITH SPECIAL REFERENCE TO SPECIATION & THEIR RESISTANCE TO VANCOMYCIN

Abstract: Introduction-Enterococci are part of the normal intestinal flora of humans and animals but have also emerged as important pathogens responsible for serious infections in hospital and community acquired infections. According to recent surveys, Enterococci remain in the top 3 most common pathogens that cause nosocomial infections. Aim-To process all the clinical samples from various departments in our hospital, for the isolation of Enterococci sp. To speciate the isolates & to have the resistance pattern of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
0
12
2
Order By: Relevance
“…Two other studies from Bangladesh reported isolation rates of E. faecalis as 62.5% by Islam and 71.18% by Akhter 14 that were almost similar to our present study. 1,14 The isolation rate of Enterococcus Faecalis from India by Mendiratta et al, 15 (85.3%) and Jada & Jayakumar et al, 5 (100%) from Kancheepuram were higher than our present study. 5,15 Reasons could be the predominance of E. fecalis in the endogenous flora of the body.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Two other studies from Bangladesh reported isolation rates of E. faecalis as 62.5% by Islam and 71.18% by Akhter 14 that were almost similar to our present study. 1,14 The isolation rate of Enterococcus Faecalis from India by Mendiratta et al, 15 (85.3%) and Jada & Jayakumar et al, 5 (100%) from Kancheepuram were higher than our present study. 5,15 Reasons could be the predominance of E. fecalis in the endogenous flora of the body.…”
Section: Discussioncontrasting
confidence: 60%
“…1,14 The isolation rate of Enterococcus Faecalis from India by Mendiratta et al, 15 (85.3%) and Jada & Jayakumar et al, 5 (100%) from Kancheepuram were higher than our present study. 5,15 Reasons could be the predominance of E. fecalis in the endogenous flora of the body. 16 After E. faecalis, 1 isolate of E. gallinarum (0.95%)has been detected among 105 isolated Enterococci in our present study.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…P.J. Desai et al (2001) found 22.19% prevalence of Enterococci in various clinical specimens, (10) whereas Susil Kumar Jada et al (2012), (11) reported the prevalence of enterococci 15.46%, among different organisms. Distribution of Enterococci positive specimens in indoors and outdoors of various departments: Indoor-266 (95%), OPD-14 (5%).…”
Section: Discussionmentioning
confidence: 99%